Strategic Adaptive Managemen for Sustainable Reconstruction and Restoration : а jointly developed teaching course by partners from Ukraine, Lithuania апа Germany : presentation - (:unkn) unknown (My University, 2025)
The presentation is devoted to the study of Strategic Adaptive Management as a key approach to ensuring sustainable recovery, reconstruction, and restoration in post-war contexts. The material covers the theoretical foundations and practical tools of adaptive management, strategic planning, and resilience-building in socio-economic and territorial systems. Special attention is paid to stakeholder engagement, risk and uncertainty management, and the integration of sustainability principles into recovery strategies. The course was jointly developed by partners from Ukraine, Lithuania, and Germany within the Transformational Learning Network for Resilience project and is intended for use as visual support for lectures as well as for independent study by higher education students.
Стратегічне адаптивне управління для сталого відновлення та реконструкції
Keywords: strategic adaptive management; sustainable recovery; sustainable reconstruction; post-war restoration; resilience; adaptive governance; strategic planning; risk and uncertainty management; stakeholder engagement; transformational learning